2016
DOI: 10.1097/ccm.0000000000001952
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Interventions to Improve Sleep on Delirium in the ICU: A Systematic Review and Research Framework*

Abstract: Although sleep interventions seem to be a promising approach for improving delirium-related outcomes, studies are limited by bias issues, varying methodologies, and multiple confounders, making the evidence base for this conclusion limited at best. Future studies would benefit from a systematic approach to studying the link between sleep intervention and delirium-related outcomes, which is outlined in the context of reviewing the existing literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 51 publications
0
44
0
Order By: Relevance
“…Atypical sleep, characterised by the absence of stage 2 markers (absence of K complexes and sleep spindles), is a form of sleep frequently observed in ICU patients [20][21][22][23]. Loss of normal sleep may alter inspiratory muscle endurance in healthy subjects [24] and possibly lead to neurobehavioral disorders such as ICU delirium [25]. However, the influence of sleep on respiratory performance and weaning duration in patients under mechanical ventilation has never previously been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Atypical sleep, characterised by the absence of stage 2 markers (absence of K complexes and sleep spindles), is a form of sleep frequently observed in ICU patients [20][21][22][23]. Loss of normal sleep may alter inspiratory muscle endurance in healthy subjects [24] and possibly lead to neurobehavioral disorders such as ICU delirium [25]. However, the influence of sleep on respiratory performance and weaning duration in patients under mechanical ventilation has never previously been studied.…”
Section: Introductionmentioning
confidence: 99%
“…C (n = 105; p < 0.05; three-way ANOVA model): Sex (F = 0; p = 0.929); age (F = 0.1; p = 0.736); admit (F = 1.8; p = 0.183) , 2016). There is also a growing number of studies demonstrating that the introduction of these organisational changes also reduces significantly the occurrence of delirium (Flannery et al, 2016;Patel et al, 2014). Usage of alternative and complementary techniques can improve the quality of sleep, too.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systemic review concluded that nonpharmacologic and pharmacologic sleep interventions may be a promising approach to improve delirium but that current research is limited by varied methodologies and significant bias, requiring a systematic approach in future research to evaluate the complex interactions between sleep interventions and delirium. 86 …”
Section: Delirium Preventionmentioning
confidence: 99%